Voices from the field: exploring practitioners' experiences and perceptions of the voices of athletes (VOA) in the pacific islands - Hong, Hee Jung; Minikin, Brian (Frontiers in Sports and Active Living, 2024)
This exploratory study aims to gain insights into practitioners' experiences and perceptions of the “Voices of Athletes” (VOA), a specialized athlete support program, developed and implemented in the Pacific Islands. Semi-structured interviews enabled participants to share detailed experiences, with 14 practitioners participating. Thematic analysis of the data identified five key themes: “Fostering Athlete Empowerment”, “Impact of Sport on Education and Social Change”, “Expanding VOA's Reach and Impact”, “VOA's Role in Preparing Athletes for Post-Sport Life”, and “Optimizing VOA Implementation and Experience”. The findings demonstrated that the VOA plays a critical role in empowering athletes and assisting them in becoming leaders within their societies. Practitioners emphasized the power of sport as an effective channel for education and inspiration, and the potential for the VOA framework to be applied in various contexts and regions. The study also revealed that the VOA helps athletes prepare for life after sport, contributing to increased self-esteem, development of transferable skills, and awareness of their social roles. The findings also emphasized the need for VOA improvements, including enhanced interactivity, larger spaces, and financial support. Recognition from sport governing bodies and coaches could broaden the program's reach and impact. Incorporating internship schemes within the VOA or related programs could address life after sport more effectively. Developing written VOA guidelines would ensure consistent, sustainable delivery, supporting its potential for wider implementation and adaptation, contributing to holistic development for athletes and young people globally.